Análisis de redistribución de planta y diseño de marco de trabajo para la implementación de 5s en Soldipintec (2024)
This project seeks to design the framework for the plant layout and 5s in the Company SOLDIPINTEC, this is a company dedicated to the metal-paint industry, mainly focused on electrostatic painting service, manufacture of welded parts and CNC plasma cutting located in Duitama - Boyacá. This contains its current distribution and an analysis of those factors that do not allow the company a good distribution so we want to seek the best performance by optimizing space, labor, machinery, raw materials, among others; making a proper plant layout. Finally, a proposal for a 5s methodology will be made to achieve improvements such as order, cleanliness, reduce waste and improve the flow of materials.